PENGARUH BUDAYA ORGANISASI, KOMUNIKASI INTERNAL DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN PT ARGA BETON GRESIK - Rohmat Aris Yunianto (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
This study aims to examine and analyze the influence of Organizational Culture, Internal Communication and Work Conflict on Employee Performance at PT Arga Beton Indah Kedamean Gresik. Data collection was carried out through questionnaires and carried out to 52 employees at PT Arga Beton Indah Kedamean Gresik. Analysis of this research data using SPSS assistance. The data testing technique used in this study is a sample technique which includes validity test with factor analysis, reliability test with Cronbach Alpha, classic assumption test which includes normality test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis to test and prove the research hypothesis. The conclusion of this study is that Organizational Culture has a significant effect on employee performance at PT Arga Beton Indah Kedamean Gresik, Internal Communication has no significant effect on employee performance at PT Arga Beton Indah Kedamean Gresik, Work Conflict has a significant effect on employee performance at PT Arga Beton Indah Kedamean Gresik . Organizational Culture, Internal Communication and Work Conflict simultaneously have a significant effect on employee performance at PT Arga Beton Indah Kedamean Gresik.